2002
DOI: 10.1097/00001756-200210070-00009
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalar activation associated with positive and negative facial expressions

Abstract: Most theories of amygdalar function have underscored its role in fear. One broader theory suggests that neuronal activation of the amygdala in response to fear-related stimuli represents only a portion of its more widespread role in modulating an organism's vigilance level. To further explore this theory, the amygdalar response to happy, sad, angry, fearful, and neutral faces in 17 subjects was characterized using 3 T fMRI. Utilizing a random effects model and hypothesis-driven analytic strategy, it was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
117
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 227 publications
(141 citation statements)
references
References 17 publications
19
117
0
5
Order By: Relevance
“…First, we found significant increases in amygdala activation in response to the perception of faces with happy, angry or fearful affect relative to the control condition. These findings are consistent with other fMRI studies in adults [38] and adolescents [20,21,39]. Second, using well-established methods of heart rate data analysis [9,34], we found a significant positive correlation between the percent signal change in the right amygdala and peak LF/HF.…”
Section: Discussionsupporting
confidence: 92%
“…First, we found significant increases in amygdala activation in response to the perception of faces with happy, angry or fearful affect relative to the control condition. These findings are consistent with other fMRI studies in adults [38] and adolescents [20,21,39]. Second, using well-established methods of heart rate data analysis [9,34], we found a significant positive correlation between the percent signal change in the right amygdala and peak LF/HF.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with a number of previous studies using a similar paradigm. Specifically, although in some studies predominantly right-sided responses were observed, irrespective of emotion (Gur et al, 2002), in others bilateral amygdala responses were found across stimulus conditions (Britton et al, 2006;Fitzgerald et al, 2006;Yang et al, 2002), similar to the present study.…”
Section: Discussionsupporting
confidence: 89%
“…For example, because both negative and positive emotions stimulate amygdala activation (e.g., Garavan, Pendergrass, Ross, Stein, & Risinger, 2001;Hamann, Ely, Hoffman, & Kilts, 2002;Yang et al, 2002), some experimenters take care to instruct participants to adopt positive mental strategies (Young et al, 2014;Zotev, Phillips, Young, Drevets, & Bodurka, 2013). Similar considerations surface concerning up-regulation of the anterior insula, which responds strongly to disgust (e.g., Phillips et al, 1997;Wicker et al, 2003), and to modifying ACC activity, which relates to a wide spectrum of cognitive processes (e.g., Bush, Luu, & Posner, 2000;Etkin, Egner, & Kalisch, 2011).…”
Section: Fmrimentioning
confidence: 99%